2012
DOI: 10.1177/0192623312453521
|View full text |Cite
|
Sign up to set email alerts
|

A Cupric Silver Histochemical Analysis of Domoic Acid Damage to Olfactory Pathways Following Status Epilepticus in a Rat Model for Chronic Recurrent Spontaneous Seizures and Aggressive Behavior

Abstract: The amnesic shellfish toxin, domoic acid, interferes with glutamatergic pathways leading to neuronal damage, most notably causing memory loss and seizures. In this study, the authors utilized a recently developed rat model for domoic acid-induced epilepsy, an emerging disease appearing in California sea lions weeks to months after poisoning, to identify structural damage that may lead to a permanent epileptic state. Sprague Dawley rats were kindled with several low hourly intraperitoneal doses of domoic acid u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Structural damage resulting from domoic acid induced status epilepticus that can alter function during the latent period has been characterized using degeneration specific cupric-silver histochemistry [31]. The most extensive damage was found in the olfactory bulb, specifically granule cells (Figure 2) and related olfactory pathways, including the anterior/medial olfactory cortices, endopiriform nucleus and entorhinal cortex (Figures S2–S6, Supplementary Information).…”
Section: Domoic Acid Epileptic Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Structural damage resulting from domoic acid induced status epilepticus that can alter function during the latent period has been characterized using degeneration specific cupric-silver histochemistry [31]. The most extensive damage was found in the olfactory bulb, specifically granule cells (Figure 2) and related olfactory pathways, including the anterior/medial olfactory cortices, endopiriform nucleus and entorhinal cortex (Figures S2–S6, Supplementary Information).…”
Section: Domoic Acid Epileptic Diseasementioning
confidence: 99%
“…Although the piriform cortex is a common site of progressive damage in both spontaneous recurrent seizures and atypical aggression, damage to cell bodies, and terminal fields of the anterior olfactory cortex was selective for aggressive rats [31]. This region has been proposed to modulate conspecific social recognition by olfactory modality [39] and the ability to distinguish conspecifics ( i.e.…”
Section: Domoic Acid Epileptic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…After determination that domoic acid-kindled SE reproducibly leads to SRS, an analysis was conducted of brain regions damaged shortly after SE. An amino cupric silver staining method found most extensive damage in the olfactory bulb and related olfactory pathways, including the anterior/medial olfactory cortices, endopiriform nucleus and entorhinal cortex (Tiedeken et al, 2013). That study concluded that dendritic spines of olfactory granule cells may be a proximal site of domoic acid action that promotes excitability of mitral cells and increases susceptibility to downstream pathways of the olfactory cortex.…”
mentioning
confidence: 92%
“…After 12 weeks, animals were euthanised and brains have been examined for indications of cell loss by using thionine (Nissl) staining, which highlights the cell bodies of all living neurons. In piriform cortex a reduced cell density has been noted in the medial layer 3 (1.3-1.8 fold decrease compared to controls), an area that shows also prominent amino cupric staining (stain that assesses neuronal damage) (Tiedeken and Ramsdell, 2013a). The same research group has reported that by following the above experimental procedure but sacrificing the rats 7 days after DomA-induced seizures intense and widespread silver reaction product in the olfactory bulb occurs, whereas minor or no evident damage is found in the hippocampus (Tiedeken et al, 2013b).…”
Section: Domoic Acid (Doma)mentioning
confidence: 99%